Pengaruh Social Media Marketing terhadap Purchase Intention dengan Consumer Trust dan Brand Image sebagai Variabel Intervening (Studi Kasus Pada Uniqlo Indonesia) - AlQodry, Muhammad Rafi Rizka; Kuswanto, Arif (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The increasing number of internet and social media users in Indonesia creates new opportunities for company marketers to sell products while at the same time building brand images and increasing consumer’s trust in their brands. Social media marketing is a marketing strategy used in the form of online networking. Of course, this opportunity is used by Uniqlo Indonesia on various social media platforms. This study aims to determine the level of influence of social media marketing on purchase intention of Uniqlo products which is mediated by trust and brand image. The research method is quantitative with the Structural Equation Modeling (SEM) analysis technique using SMARTPLS 4 software. This research consists of four variables, namely Social Media Marketing as an independent variable, Purchase Intention as the dependent variable, Consumer Trust and Brand Image as intervening or mediating variables. Based on the results of the study, social media marketing has a positive and significant effect on consumer trust, social media marketing has a positive and significant effect on brand image, social media marketing has a positive and significant effect on purchase intention, consumer trust has a positive and significant effect on purchase intention, brand image has an effect positive and significant impact on purchase intention, mediating impact of consumer trust from social media marketing on purchase intention, and mediating impact of brand image from social media marketing on purchase intention.